INDIAN SPINACH LEAF POWDER AS ADSORBENT FOR MALACHITE GREEN DYE REMOVAL FROM AQUEOUS SOLUTION - Atoyebi, Omolara Mustophat; Bello, 1Olugbenga Solomon (Covenant Journal of Physical and Life Sciences, 2014)
Indian spinach leaf powder (ISLP) was used as an adsorbent for the removal of malachite green (MG) dye from aqueous solution. Adsorption characteristics of the adsorbent were studied using Fourier Transform Infrared spectroscopy. Operational parameters such as initial dye concentration and temperature were studied in batch systems. Experimental data were analysed using Langmuir and Freundlich isotherms and it was found that Freundlich isotherms model fitted the adsorption data most. Adsorption rate constants were determined using pseudo first-order and pseudo-second-order model equations. The result clearly showed that the adsorption of MG dye on ISLP followed pseudo-second-order kinetics model. Thermodynamic functions Î”Go, Î”Ho, Î”So were obtained. The adsorption process was found to be endothermic and non-spontaneous. The study shows that ISLP is a good precursor for MG dye removal. Keywords: Indian spinach leaf powder, Malachite Green, Adsorbent, Spontaneous, endothermic.